The influence of occult infection with hepatitis B virus on liver histology and response to interferon treatment in chronic hepatitis C patients - Silva,Claudia da (2004)
Occult hepatitis B virus (HBV) infections have been identified in patients with chronic hepatitis C virus (HCV) infection, although the clinical relevance of occult HBV infection remains controversial. We searched for serum HBV DNA in 106 HBsAg negative/anti-HBc positive patients with chronic HCV infection and in 150 blood donors HBsAg negative/anti-HBc positive/anti-HCV negative (control group) by nested-PCR. HCV genotyping was done in 98 patients and percutaneous needle liver biopsies were performed in 59 patients. Fifty-two patients were treated for HCV infection with interferon alone (n=4) or combined with ribavirin (n=48) during one year. At the end and 24 weeks after stopping therapy, they were tested for HCV-RNA to evaluate the sustained virological response (SVR). Among the 106 HCV-positive patients, 15 (14%) were HBV-DNA positive and among the 150 HCV-negative blood donors, 6 (4%) were HBV-DNA positive. Liver biopsy gave a diagnosis of liver cirrhosis in 2/10 (20%) of the HBV-DNA positive patients and in 6/49 (12%) of the HBV-DNA negative patients. The degree of liver fibrosis and portal inflammation was similar in HCV-infected patients HBV-DNA, irrespective of HBV-DNA status. SVR was obtained in 37.5% of the HBV-DNA positive patients and in 20.5% of the HBV-DNA negative patients; this difference was not significant. In conclusion, these data suggested that occult HBV infection, which occurs at a relatively high frequency among Brazilian HCV-infected patients, was not associated with more severe grades of inflammation, liver fibrosis or cirrhosis development and did not affect the SVR rates when the patients were treated with interferon or with interferon plus ribavirin.